Strength in Numbers? Gender Composition, Leadership, and Women's Influence in Teams - Christopher F. Karpowitz; Stephen D. O'Connell; Jessica Preece; Olga B. Stoddard (Institute of Labor Economics (IZA), 2023)
Policies that increase women's representation often intend to provide women with influence over processes and decisions of the organization in which they are implemented. This paper studies the effect of gender composition and leadership on women's influence in two field experiments. Our first study finds that male-majority teams accord disproportionately less influence to women and are less likely to choose women to represent the team externally. We then replicate this finding in a new context and with a larger sample. To investigate the relationship between formal leadership and women's influence and authority, the second study also varied the gender of an assigned team leader. We find that a female leader substantially increases women's influence, even in male-majority teams. With a model of discriminatory voting, we show that either increasing the share of women or assigning a female leader reduces the rate at which individual teammates discriminate against women by more than 50%. These conditions both increase the influence of women and improve women's experience in work teams by creating an institutional environment that reduces the expression of discriminatory behavior at the individual level.
Keywords: J16; 330; gender; field experiment